The Effect of Online Games on Physical Activity of Students Universitas Pendidikan Indonesia - Marsha Ayu Rizkika; Isti Kumalasari; Widya Astuti; Fajria Saliha Puspita Prameswari (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
Background The rise of digital technology has led to a higher prevalence of online game addiction, particularly among university students. This phenomenon is believed to influence several aspects of student lifestyle, including screen time, physical activity, junk food consumption, and overall nutritional status. Objective This study aims to analyze the relationship between online game addiction and variables such as screen time, physical activity levels, junk food consumption, and nutritional status among students at Universitas Pendidikan Indonesia. Method A cross-sectional approach was employed, involving 82 students chosen proportionally from nine faculties at Universitas Pendidikan Indonesia. Data were gathered using the Game Addiction Scale, a screen time questionnaire (QUEST), a Food Frequency Questionnaire for junk food, and BMI calculations to assess nutritional status. The collected information was analyzed with the Spearman correlation test. Results The findings revealed a significant negative correlation between online game addiction and physical activity levels (p = 0.020; r = -0.256). However, no direct association was observed between online game addiction and screen time, junk food consumption, or nutritional status. Conclusion Students exhibiting signs of online game addiction are more likely to have lower physical activity levels. However, the addiction does not directly impact screen time, unhealthy food consumption, or individual nutritional status.